2019
DOI: 10.12681/healthresj.19641
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between nursing workload and bloodstream infection from central venous catheter in ICU

Abstract: Introduction: Bloodstream infection associated with the presence of central venous catheters is the second most common hospital infection in the Intensive Care Unit (ICU). The nursing stuff is an essential part of the human resources of the ICU which contributes substantially to provide holistic and effective care to critically ill patients. The level of the nursing workload and its possible influence on the clinical course and outcome of critically ill ICU patients has been systematically studied in recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Regarding NW of patients’ first-day admission in the ICU, it was 65.15 ± 13.05, where there is a significant increase in the average value of NAS. Similar values were found in Michali et al’s study [ 3 ]. The average time of nursing care was calculated in minutes and this was found to correspond to 789.26 ± 33.7 min, a value much lower than in Dede et al’s study [ 4 ], which was 948.89 ± 103.60 min.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Regarding NW of patients’ first-day admission in the ICU, it was 65.15 ± 13.05, where there is a significant increase in the average value of NAS. Similar values were found in Michali et al’s study [ 3 ]. The average time of nursing care was calculated in minutes and this was found to correspond to 789.26 ± 33.7 min, a value much lower than in Dede et al’s study [ 4 ], which was 948.89 ± 103.60 min.…”
Section: Discussionsupporting
confidence: 92%
“…The above measurements were compared with those recommended by the Federal Council of Nursing (COFEN Resolution 293/2004) and correspond to the 17.9-h minimum average percentage of NAS that seems to belong to the established parameters. The present study therefore revealed a relatively low NW on a daily basis [ 3 , 4 , 21 , 26 ].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations